2003
DOI: 10.1016/s0002-9440(10)63466-9
|View full text |Cite
|
Sign up to set email alerts
|

Complement C5 in Experimental Autoimmune Encephalomyelitis (EAE) Facilitates Remyelination and Prevents Gliosis

Abstract: Activation of the classical complement system is known to play a central role in autoimmune demyelination. We have analyzed the role of complement component C5 in experimental autoimmune encephalomyelitis (EAE) using C5-deficient (C5-d) and C5-sufficient (C5-s) mice. Both groups of mice displayed early onset EAE, a short recovery phase, and similar stable chronic courses. However, in contrast to the clinical similarities, marked differences were apparent by histopathology. During acute EAE in C5-d, a delay in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 59 publications
7
44
0
Order By: Relevance
“…The specificities for anti-VCAM1 and anti-TIE2 antibodies have been shown previously (Weerth et al, 2003;Cho et al, 2004, respectively). Acetonefixed cryosections were used for anti-PECAM1 and anti-TIE2 staining, whereas PFA-fixed, deparaffinized sections were used for anti-VCAM1-and anti-HIF1␣-staining.…”
Section: Immunohistochemistry and Immunoblottingsupporting
confidence: 57%
“…The specificities for anti-VCAM1 and anti-TIE2 antibodies have been shown previously (Weerth et al, 2003;Cho et al, 2004, respectively). Acetonefixed cryosections were used for anti-PECAM1 and anti-TIE2 staining, whereas PFA-fixed, deparaffinized sections were used for anti-VCAM1-and anti-HIF1␣-staining.…”
Section: Immunohistochemistry and Immunoblottingsupporting
confidence: 57%
“…Expression of this receptor has also been reported on neurons and astrocytes (Gasque et al, 1995;Van Beek et al, 2000). The dual role of C5 in enhancement of inflammatory demyelination in acute EAE and promoting remyelination in recovery in the CNS has been recently proposed (Weerth et al, 2003). Furthermore, it was shown that the C5 complement component can protect oligodendrocytes from apoptosis in the recovery phase of EAE (Niculescu et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…CR3 or Mac-1) attenuates the severity of EAE and reduces leukocyte infiltration into the CNS, while transgenic expression of C3a in the CNS markedly exacerbates EAE (Boos et al, 2004;Bullard et al, 2005;Nataf et al, 2000). In contrast deletion of C5, C5-derived fragments, and their associated receptors has no effect on the course of EAE (Reiman et al, 2002;Reiman et al, 2005;Weerth et al, 2003). Pharmacological inhibition of the C5a receptor also fails to lessen the severity of EAE (Morgan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%